PSYCHOLOGICAL IMPACT OF SHARENTING A COMPREHENSIVE REVIEW - Santhosh Kumar, Ramachandran, Arun James, (EPRA International Journal of Multidisciplinary Research (IJMR), 2023)
In the digital age, the practice of sharenting, where parents share their children's photos and personal information on social media, has become ubiquitous. This article presents a comprehensive review of the psychological impact of sharenting, delving into the motivations behind it, the types of content shared, and its consequences on children's privacy, self-esteem, and parent-child relationships. It explores the ethical considerations and offers guidelines for responsible sharenting practices, emphasizing the importance of protecting children's digital privacy.